Philosophy for children and philosophy with children: an inspiring experience in thinking about mathematics - Piracoca, Yuli; Mariño, Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The article presents the results of the project Transformation of mathematics learning from philosophy for/with children, developed at the Institución Educativa Agropecuaria el Escobal, in the municipality of Ramiriquí. The objective was to analyze the contribution of Philosophy for/with Children in the mathematics learning process of the participating students. The research method was qualitative with a critical-social approach. The study was developed in four moments: theoretical approach, documentation of the need, application of the experience and analysis. The results are divided into four sections: voices to think about mathematics, making thoughts and dialogues visible; a space for emancipation and autonomy, which exposes interests and ways of understanding mathematics; the care of oneself, of the other and of the other present in mathematics and philosophy makes factors implicit in the mathematical situations presented visible; the learning communities. An experience with mathematics emphasizes collaborative work, philosophical dialogue, questioning and investigating. In conclusion, it is possible to strengthen the learning process of mathematics through philosophizing.